Frequency of hepatocellular carcinoma in cirrhotic patients with hepatitis-C virus positive patients in Karachi-Pakistan - Tariq, Muhammad; Ahad, Wajeeha; Tahir, Muhammad; Ahmed, Ayaz; Shafique, Hafeez Muhammad (International Journal of Research in Medical Sciences, 2017)
Background: Hepatocellular Carcinoma is the 5th most common neoplasm in the world and 4th most common cancer death. Most patients with HCC have an underlying chronic liver disease (often cirrhosis), resulting mainly from chronic infection by Hepatitis B Virus (HBV), Hepatitis C Virus (HCV), excessive alcohol consumption, and often an association of these causes. HCC has recently gained more interest due to its increasing incidence in industrialized countries. Objective: To determine the frequency of hepatocellular carcinoma in hepatitis C reactive cirrhotic patients. Methods: Place and duration of study: Department of medicine, civil hospital Karachi. Duration: Six months from 16-12-2012 to 15-6-2013. Subjects and methods: Patients admitted in medical wards of civil hospital Karachi with liver cirrhosis due to hepatitis C virus were included in the study. Investigation relevant to hepatocellular carcinoma like alpha fetoprotein and ultrasound was performed. If the Alpha fetoprotein is greater, then 200 ng/ml in the setting of a mass in a cirrhotic liver the likelihood of hepatocellular carcinoma is greater then 90% and biopsy is not required. Results: Overall mean age was 41.1 ± 7.1 years with Male:Female = 4.2:1. Out of 141 cases; hepatocellular carcinoma was diagnosed in 8 (5.7%) of patients with HCV related cirrhosis with mean age 48.6 ± 6.4 years. Proportion of hepatocellular carcinoma was high 7 (6.1%) in male. 7 (6.4%) cases had child pugh-C, 1 (5%) case had child pugh-B and while no HCC was seen in child pugh-A. Conclusion: In this study hepatocellular carcinoma was 5.7% in cases with hepatitis-C induced cirrhosis. Older age (>54 years), male sex and child pugh-C were predominant factors leading to hepatocellular carcinoma.